PROBLEMS OF TRADE AND ECONOMIC RELATIONS OF WEST AFRICAN COUNTRIES WITH THE EUROPEAN UNION, PROSPECTS FOR THEIR DEVELOPMENT - N. B. Sekongo (Publishing House of the State University of Management, 2020)
The problems of trade and economic relations between West African countries and the European Union have been considered in the article in detail, a brief description of the Economic Community of West African States has been given. The essence of relationships between West Africa and the European Union based on the papers, both foreign and domestic researchers in the field of security, regional economic development and integration etc. has been disclosed. The historical path within the framework of international legal documentation that preceded the signing of the Economic Partnership Agreement has been described. The conducted study was based on the analysis of the cost dynamics of exports, imports and trade balance, their structure has been briefly adduced. The main negative aspects faced by West African countries in connection with the implementation of the Economic Partnership Agreement, in particular tariff restrictions, the ban on the use of export taxes, which undermines the national sovereignty of the Economic Community of West African States, have been revealed. Nevertheless, the signed Agreement will allow West Africa to actively integrate into world trade, improve the economic and demographic situation, while the overall trade tariff will remain at the same level.